Internet of Things and the Future of Manufacturing Industry - Jayaraman, R.; Basu, Avisek; Chakraborty, Suryadipta (Indian Journal of Computer Science, 2018)
Manufacturing companies are evolving into highly interconnected, multimodal, aggregated, agile networked entities knitted together by IT systems. The latest development in IT, the Internet of Things or IoT, is slowly beginning to change the traditional methods of manufacturing. Next on the horizon is the Industry 4.0 (I - 4.0) model, which will be created by using a mix of cloud computing, wireless connectivity, AI, and computer integrated manufacturing. The underlying automation is provided by the IoT, using sensors, which collect data, and feed into an interconnected grid of multiple action nodes which will drive production, productivity, and efficiency. In this paper we address the issues that will govern the adoption of IoT in manufacturing. We show that the I - 4.0 will be highly dependent on IoT, will use data analytics using big data and AI to process large volumes of data to provide agile output. The cost considerations which will form a key part of the transition to the I - 4.0 era are also discussed using a model.